Development of Assessment Instrument for Singing Skills and Playing Musical Instrument for The Music Teacher Candidates of General Schools (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
The competences of music teacher candidates in teaching singing practice and playing a musical instrument are needed in the teaching-learning process at general schools. Hence, the process needs a comprehensive preparation for both competences. The objective of this study is to prepare an assessment instrument of singing practice and playing a musical instrument which is needed to assess the competences of music teacher candidates. The study used mix-method approach. The combination of qualitative and quantitative is required as the two methods are interrelated for both in the process of preparing assessment instruments and testing the instrument. The instruments consist of nine assignments. The six of which are the instruments for reading melodic and rhythmic notation and the other three instruments are to assess the skills to accompany songs. Based on the result, it can be found that the coefficient of instrument reliability is 0.817 in the type of consistency definition and 0.810 in the type of absolute agreement definitions. It can be concluded that the instrument made by using the analytic rubric of coefficient the reliability is better compared to the instrument made by a holistic rubric.